2019
DOI: 10.1002/dev.21835
|View full text |Cite
|
Sign up to set email alerts
|

RSA reactivity in response to viewing bullying film and adolescent social adjustment

Abstract: This study assessed adolescent respiratory sinus arrhythmia (RSA) reactivity while watching a bullying film clip from Boyz'n the Hood. We emphasized the importance of considering measurement context of RSA and examined whether RSA reactivity moderated the links between environmental factors (i.e., neighborhood violence, parental psychological control, and parental acceptance) and adolescent social adjustment. Data were collected from 57 adolescents and their primary caregivers.Electrocardiogram (ECG) and respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 77 publications
0
15
0
1
Order By: Relevance
“…Third, the results showed that an increase in maternal RSA from baseline to task was positively associated with positive parenting. Previous research has shown that positive parenting is associated with both RSA activation and withdrawal (Leerkes et al, 2017;Lorber & O'Leary, 2005;Moore et al, 2009;Shaffer et al, 2018), but some researchers have argued that different types of tasks and contexts place different demands on physiological systems, and therefore adaptive RSA responses may look different in different contexts (Connell et al, 2017;Cui et al, 2019). For example, RSA withdrawal has been associated with adaptive functioning during stressful tasks (Balzarotti et al, 2017;Connell et al, 2017), but RSA activation has been associated with adaptive functioning and efforts to engage in self-regulation in positive social interactions and to recover from stress (Balzarotti et al, 2017;Butler et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the results showed that an increase in maternal RSA from baseline to task was positively associated with positive parenting. Previous research has shown that positive parenting is associated with both RSA activation and withdrawal (Leerkes et al, 2017;Lorber & O'Leary, 2005;Moore et al, 2009;Shaffer et al, 2018), but some researchers have argued that different types of tasks and contexts place different demands on physiological systems, and therefore adaptive RSA responses may look different in different contexts (Connell et al, 2017;Cui et al, 2019). For example, RSA withdrawal has been associated with adaptive functioning during stressful tasks (Balzarotti et al, 2017;Connell et al, 2017), but RSA activation has been associated with adaptive functioning and efforts to engage in self-regulation in positive social interactions and to recover from stress (Balzarotti et al, 2017;Butler et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Fast Fourier transformation was used to extract values in the 0.23 to 0.5 frequency band (an age-appropriate respiratory frequency band for this adolescent sample; Cui, Zhang, Houltberg, Criss, & Morris, 2019; Shader et al, 2018). Both the resting task and the conflict task were split into 1-minute epochs; thus, HF-HRV values were obtained for every 1-minute epoch.…”
Section: Methodsmentioning
confidence: 99%
“…For example, less RSA reactivity (less withdrawal) to emotional video stimuli has been found to act as a differential susceptibility factor, associated with more problems in contexts of greater maternal rejection (Wagner et al, 2018b) marital conflict (Obradovic et al, 2011), and community violence (Cui et al, 2019), and with fewer problems in less aversive contexts, whereas these environmental factors were not associated with problems for greater RSA withdrawal. Conversely, El-Sheikh et al (2001), El-Sheikh andWhitson 2006) and Katz and Gottman (1997) found that less RSA reactivity acted as a diathesis, being associated with more problems for children who experienced more marital conflict, but not fewer problems than average in the absence of conflict; marital conflict did not predict problems when RSA withdrawal was greater.…”
Section: Rsa Reactivity In Biopsychosocial Models Of Developmentmentioning
confidence: 99%